Does Security Play a Role in European Development Aid Policy? - Tilman Brück; Olaf J. de Groot; Guo Xu (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
In this Policy Briefing we address the question of whether there is a coherent and consistent policy when it comes to giving development aid. While one would theoretically argue that aid provision should be based on objective criteria set out to optimize governments' behavior or people's welfare, we find that this is not the case. While specific countries may be optimizing their objectives in international aidgiving, the cumulative effect, particularly when it comes to European policy is incoherent and inconsistent. Coordinating development policy at the European level could alleviate this problem.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330